Transformational Leadership and Organizational Citizenship Behavior: Exploring the mediation of Organizational Learning Culture and Organizational Justice - Nanang A.S; Margono Setiawan; Djumilah Hadiwidjojo; Idris Idris (Universitas Negeri Malang, 2021)
Organizational citizenship behavior (OCB) manifested from employees’ positive-social behaviors that have been getting popular and beneficial to individuals and organizations, especially in the context of nurses in hospitals who are likely to works beyond the call of duties. The current study attempts to measure the mediation effects of organizational learning culture (OLC) and organizational justice (OJ) in the influence of transformational leadership (TFL) toward OCB among nurses. The current study uses questionnaires distributed to nurses in the public hospital, Tuban, Indonesia. A total of 205 out of 208 responses were collected. Then, partial least squares (PLS) were employed to examine the proposed hypothesis. The results reveal that OLC and OJ are significant predictors to promote OCB. Surprisingly, TFL does not show a significant implication on OCB. In addition, the findings of the current research prove that both OLC and OJ completely mediate the relationship between TFL and OCB. This study also proposes that managers have to encourage learning and create a fair environment in fostering employees to exhibit OCB frequently.